Multinucleon Transfer in Peripheral Collisions of 64Ni on 64Ni at 25 MeV/nucleon - Kontogianni, Eirini; Souliotis, Georgios A.; Giannitsa, Chrysi; Gkatzogias, Konstantinos; Koulouris, Stergios; Travlou, Eleftheria; Veselsky, Martin; Yennelo, Sherry J.; Bonasera, Aldo (HNPS Advances in Nuclear Physics, 2026)
We study the yields, the momentum distributions and the angular distributions of projectile-like fragments from peripheral collisions of 64Ni (25 MeV/nucleon) on 64Ni. The experimental data were obtained in previous works with the BigSol separator system at the Cyclotron Institute of Texas A&M University. Projectile fragments were collected and analyzed at forward angles (1.5-3.0 degrees). The production cross sections, the momentum distributions and the angular distributions of the fragments were systematically studied and compared with the Deep-Inelastic Transfer (DIT) model and the Constrained Molecular Dynamics (CoMD) model followed by the deexcitation model GEMINI. Both models appear to describe the data rather adequately, but possible improvements are necessary. Special attention is given in the possibility to produce neutron-rich rare isotopes of elements at the beginning of the astrophysical r-process. Efforts similar to this work are ongoing to shed light to the reaction mechanisms of peripheral collisions at this energy (25 MeV/nucleon).